Genetic studies of yield and quality traits in Indian mustard (Brassica juncea L.) (Journal of Oilseed Brassica, 2026)
To study the heterosis, combining ability and components of genetic variance for seed yield and 11 quantitative, and qualitative characters in 40 F1s of Indian mustard resulting from 10 lines and 4 testers along with standard check GM 3 were sown in a Randomized Block Design with three replications at Main Castor–Mustard Research Station, Sardarkrushinagar during Rabi 2012-13. Analysis of variance revealed the significant differences among genotypes for all the traits. The gca and sca variances were significant for all the traits. The ó2 gca and ó2 sca ratio indicated that non-additive gene action was predominant in the inheritance of all the traits except, plant height and number of siliquae per plant. The parents SKM 0518, SKM 0907 and SKM 0445 were good combiners for seed yield per plant. Besides among these parents SKM 0518 was also good general combiner for days to flowering, days to maturity, number of siliquae per plant, oleic acid, erucic acid and glucosinolate content. The estimates of sca effects indicated that the cross combinations SKM 0820 x GDM 4 (15.5) followed by SKM 0715 x SKM 0445 (13.5) and SKM 0907 x SKM 0445 (12.5) were significant for seed yield per plant. The cross SKM 0820 x GDM 4 registered high per se performance, standard heterosis and sca effects for seed yield per plant. Considering mean performance, heterosis and combining ability effects, parents SKM 0518, SKM 1013, SKM 0445 and SKM 0904 and hybrids SKM 0820 x GDM 4, SKM 0907 x SKM 0445 and SKM 0715 x SKM 0445 were found promising for the development of high yielding genotypes. The results revealed that breeding approaches like biparental mating followed by recurrent selection, diallel and line x tester selective mating design etc., are suggested to identify desirable transgressive segregants for further improvement of these traits.